Adherence to and persistence with lacosamide, perampanel, lamotrigine, and levetiracetam in adult patients with focal epilepsy in Japan: A descriptive cohort study using a claims database. Issue 4 (April 2023) - Chen, Siming; Fukasawa, Toshiki; Ikeda, Akio; Takeuchi, Masato; Shimotake, Akihiro; Yoshida, Satomi; Kawakami, Koji
Abstract: Objective: We evaluated adherence to and 1-year persistence of two third-generation anti-seizure medications (ASMs), lacosamide and perampanel, in adult patients with focal epilepsy, compared with lamotrigine and levetiracetam. Methods: A cohort study was conducted using a Japanese health insurance claims database (JMDC Inc.). We identified patients with adult-onset focal epilepsy who initiated any of the four ASMs between August 31, 2016, and October 31, 2019. Patients were further classified into ASM-naïve patients initiating any of the four ASMs as first-line treatment, and ASM-experienced patients initiating any of the four ASMs as second- or later-line treatment. Outcomes included adherence (proportion of days covered [PDC], defined as the total number of days covered by ASMs divided by the total number of days in the follow-up period) and 1-year persistence for the four ASMs. Results: We identified 141 lacosamide, 75 perampanel, 80 lamotrigine, and 530 levetiracetam initiators. Among these, the proportion of ASM-naïve patients was highest in the levetiracetam group (60.8%), followed by the lamotrigine (25.0%), lacosamide (20.6%), and perampanel groups (1.3%). Mean PDC (standard deviation) was similar across the four groups, at 0.95 (0.08) for lacosamide, 0.93 (0.12) for perampanel, 0.92 (0.10) for lamotrigine and 0.94 (0.11) for levetiracetam. The proportion of patients persisting with treatment for 1 year was highest in the lacosamide group (73.0%), followed by the levetiracetam (58.3%), lamotrigine (57.5%), and perampanel groups (54.7%). In ASM-naïve patients, adherence and 1-year persistence were almost identical in the lacosamide, lamotrigine, and levetiracetam groups. Results for ASM-experienced patients did not significantly differ from those of all patients. Significance: With regard to adherence and 1-year persistence, lacosamide may be equal to or better than lamotrigine and levetiracetam, especially in patients with experienced ASM, while perampanel may be comparable to lamotrigine and levetiracetam in patients with experienced ASM.